The Role of PET-CT-Guided Metabolic Biopsies in Improving Yield of Inconclusive Anatomical Biopsies: A Review of 5 Years in a Teaching Hospital - Dharmender Malik; Vineet Pant; Ishita Sen; Parul Thakral; Subha Shankar Das; Virupakshappa CB (Diagnostics, 2023)
Tumour sampling is indispensable to diagnostic and therapeutic decision making. Thus, 18F-FDG PET/CT has the potential to accurately discriminate between viable and non-viable tissues due to its ability to characterise the metabolism of visible tissues. This study’s objective was to evaluate the incremental utility of 18F-FDG PET-CT-guided metabolic biopsy in individuals with suspected lesions and a previous negative anatomical biopsy. This study included a total of 190 consecutive patients with probable malignancy and who had experienced a previous unsuccessful anatomical biopsy who underwent PET-CT-guided metabolic biopsy. We retrospectively analysed the patients’ medical records and imaging investigations to assess demographics, complications, pathologies, and final clinical diagnoses. Using multivariate logistic regression, correlation between several confounding factors that lead to post-procedural problems was evaluated. Adequate material was obtained in all patients, and 162 (85%) were found to be positive for malignancy with a diagnostic yield of 96.9%. In 25 (13.1%) patients, post-procedural complications were reported, with pneumothorax being the most prevalent issue. In evaluating oncological patients, metabolic biopsy provides a safer alternative therapy with a high diagnostic yield and comparable complications. PET-CT, being an essential component of cancer staging, may serve as a one-stop shop for the management of these patients’ conditions.